Pengaruh Metode Bernyanyi Terhadap Kemampuan Mengingat Pada Mata Pelajaran IPA Siswa Kelas V SD Negeri 46 Kota Pagaralam - Pertiwi, Melda; Kariyanto, Hendi (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to determine the effect of the singing method on the ability to remember in science subjects for fifth grade students of SD Negri 46 Pagaralam City. The type of research used is Quantitative with Experimental model, Pre-Experimental Design design One Group Pre-Test Post-test. The sample was all fifth grade students of SD Negri 46 Pagaralam with a total of 24 students. The sampling technique is purposive sampling, data collection techniques observation, documentation, interviews, tests. The data analysis test uses normality, homogeneity, hypothesis testing and the coefficient of determination. Based on the results of the paired sample test data by looking at the number of Df 23, therefore the provisions in the t distribution table apply, the researcher takes 2.069 as a reference in comparing a table with the provisions if tcount> ttable (tcount 54.070> ttable 2.069) then Ho is rejected Ha is accepted. It can be concluded that Ha is accepted, meaning that there is an effect of the singing method on the ability to remember in science subjects of fifth grade students of SD Negri 46 Pagaralam City. The calculation of the coefficient of determination R2 R Square value of 0.912 shows that the singing method affects the ability to remember by 91.2%.